Efficacy and safety of direct oral anticoagulants for treatment of left ventricular thrombus; a systematic review. Issue 8 (10th November 2021) - Kumar, Dilpat; Warsha, F. N. U.; Helmstetter, Nicholas; Gupta, Vishal
Abstract: Introduction: Left ventricular thrombus (LVT) is a well-recognised complication of ischaemic and non-ischaemic heart disease. The incidence of this complication has drastically reduced due to reperfusion therapies. Current guidelines recommend using warfarin for at least three months. But, direct-acting oral anticoagulants (DOACs) are increasingly used as an off-label alternative to vitamin K antagonists (VKA) to treat LVT. In this article, we will review the use of DOACs for the treatment of LVT. Methods and results: We conducted a literature search for published case series, meta-analyses, and review articles in four electronic databases: PubMed, EMBASE, OVID, and Google Scholar from inception until 1 August 2020. Fifteen articles including meta-analyses, review articles and case series were included. A total of 292 patients with LVT from 7 articles are analysed. The majority ( n  = 110) were treated with rivaroxaban followed by apixaban ( n  = 86), and warfarin (60). 26 patients from 292 were not included in the analysis. Of the 206 patients on DOACs, 180 (87.3%) had resolution of LVT. 22 had persistent LVT. Six patients had reported bleeding. Three patients had gastrointestinal (GI) bleeding. One patient had pulmonary haemorrhage while one other had epistaxis requiring blood transfusion. Five of six patients who had bleeding were on either single or dual antiplatelet therapy in addition to DOAC. One patient had reported a cardioembolic stroke while on a DOAC. Median follow-up duration varied from one month to two years. Conclusion: Based on our review, DOACs are likely to be at least as effective and safer as VKA for stroke prevention and thrombus resolution in patients with LVT.